TRANSFORMATION IN 21ST CENTURY EDUCATION: DIGITAL PEDAGOGY AND LEARNER-CENTERED TEACHING TRENDS - Sojida Umirzakovna Allayarova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the transformative shifts in 21st-century education driven by the integration of digital technologies and learner-centered pedagogy. It highlights the paradigm shift from traditional teacher-centered instruction to personalized, technology-enhanced, and student-driven learning experiences. Theoretical underpinnings such as humanism, social constructivism, and connectivism are examined to provide a foundation for understanding digital pedagogy. Key components of this transformation include adaptive learning environments, inclusive practices, student motivation, and evolving roles of educators. The study emphasizes that digital pedagogy not only involves the use of tools but requires a complete reimagining of educational practices, assessment strategies, and teacher professional development. Drawing from international best practices and research, the article concludes that the future of education lies in the intentional and critical use of digital technologies to promote equity, creativity, and lifelong learning.